PARADIGMA KEKUATAN PROPAGANDA RADIKALISME DALAM KESENJANGAN EKONOMI MASYARAKAT KAMPUS - Ilmika Noer Humaedi; Al Husna; Fahra Putri Wulandari; Regina Candrika; Shakhilla Wijayanti Putri; Muhamad Parhan (Jurnal Ilmiah Wahana Pendidikan, 2023)
Radicalism is a complex problem, so there is a need for a deeper understanding of the factors that cause radicalism, one of which is economic disparity. Radicalism and economic disparity are two phenomena that are interrelated and can significantly affect the social conditions of the campus community. In this case, our research aims to analyze an article entitled The Power Paradigm of Radicalism Propaganda in the Economic Gap of Campus Communities. The research method used is a qualitative research method using data collection techniques through observation and literature review. The results of this study indicate that radicalism propaganda uses various ways to influence and recruit the campus community, including by utilizing economic topics in the campus community. Therefore, by making an article about the Power Paradigm of Radicalism Propaganda in the Economic Gap of the Campus Communities, it is hoped that it can participate in providing efforts to prevent radicalism in the campus community, as well as improve social quality and security in the campus environment.